2022
DOI: 10.5194/tc-16-1845-2022
|View full text |Cite
|
Sign up to set email alerts
|

Towards accurate quantification of ice content in permafrost of the Central Andes – Part 1: Geophysics-based estimates from three different regions

Abstract: Abstract. Increasing water scarcity in the Central Andes due to ongoing climate change recently caused a controversy and debate on the significance of permafrost occurrences for the hydrologic cycle. The lack of comprehensive field measurements and quantitative data on the local variability in internal structure and ground ice content further exacerbates the situation. We present field-based data from six extensive geophysical campaigns undertaken since 2016 in three different high-altitude regions of the Cent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 68 publications
0
53
0
Order By: Relevance
“…The bedrock is in general highly fractured as a result of the numerous fault systems that cross the area (Devine et al, 2019). The results of the geophysical surveys presented in Part 1 (see Hilbich et al, 2022a) point to largely homogeneous subsurface conditions with significant ground ice occurrences (mostly in terms of a thin, icerich layer varying in thicknesses of approximately 2-5 m). Furthermore, ground ice is expected to be present as well in the highly fractured and hydrothermally altered bedrock at greater depths .…”
Section: Rock-glacier-free Site -Site Dmentioning
confidence: 93%
See 4 more Smart Citations
“…The bedrock is in general highly fractured as a result of the numerous fault systems that cross the area (Devine et al, 2019). The results of the geophysical surveys presented in Part 1 (see Hilbich et al, 2022a) point to largely homogeneous subsurface conditions with significant ground ice occurrences (mostly in terms of a thin, icerich layer varying in thicknesses of approximately 2-5 m). Furthermore, ground ice is expected to be present as well in the highly fractured and hydrothermally altered bedrock at greater depths .…”
Section: Rock-glacier-free Site -Site Dmentioning
confidence: 93%
“…Due to the lack of in situ investigations and subsurface information, commonly a mean volumetric ice content of 40 % to 60 % is assumed for the entire rock glacier area (Brenning, 2005;Rangecroft et al, 2015;Bodin et al, 2010;Azócar and Brenning, 2010;Rangecroft et al, 2015;Jones et al, 2019). This can be problematic as the ground ice content of rock glaciers has been shown to vary considerably from case to case (Arenson and Jakob, 2010;Hauck et al, 2011;Mollaret et al, 2020;Halla et al, 2021;Hilbich et al, 2022a) and also along longitudinal profiles of a single rock glacier (Jones et al, 2019;Halla et al, 2021). Furthermore, while rock glaciers are the focus of several studies assessing the hydrological importance of permafrost in semiarid regions, knowledge about the permafrost distribution outside of rock glaciers is still extremely limited (Arenson and Jakob, 2010;Duguay et al, 2015) even though ice-rich permafrost has been shown to be present in areas devoid of rock glaciers (García et al, 2017;Schaffer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations